Dzieciństwo i język w prozie Pascala Quignarda: o fikcję w teorii - Thiel-Jańczuk, Katarzyna (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
With regard to the notion of infans understood by Michel de Certeau as the unconscious and the knowledge beyond language, as well as etymologically linked with the French word enfant, a child, and with reference to contemporary reflection connected with the return of literary fiction to social sciences (on the example of literature applied to psychoanalysis of Pierre Bayard), the author of the text sees Quignard’s prose as a critique of rational language recognizing literary fiction as a primal form of epistemological discourse.
Keywords: dzieciństwo; literatura; epistemologia; teoria; fikcja; Pascal Quignard